Assessing the macroeconomic and social impacts of slow steaming in shipping: A literature review on small island developing states and least developed countries - Seyedvahid Vakili; Fabio Ballini; Alessandro Schönborn; Anastasia Christodoulou; Dimitrios Dalaklis; Aykut I. Ölçer (Journal of Shipping and Trade (JST), 2023)
The International Maritime Organisation (IMO) has adopted the Energy Efficiency Existing Ship Index (EEXI) and the Carbon Intensity Indicator (CII) as short term measures for decarbonisation of the shipping industry; the IMO also made the collection of relevant data and associated reporting of the indicator mandatory from January 2023. However, many existing ships do not meet the EEXI and CII "targets" and cannot invest in other technologies to meet the relevant requirements. Given the various barriers to energy efficiency, the application of slow steaming may be a measure to effectively meet EEXI and CII requirements. A qualitative systematic literature review was conducted on the potential macroeconomic and social impacts of slow steaming on states, with a special focus on Small Island Development States and Least Developed Countries, when used as the primary modality of reducing GHG emissions from shipping. This effort includes peer-reviewed studies and studies from the gray literature, many of which include examples that borrow data from the aftermath of the economic crisis that was manifested in 2008. The vast majority of those studies is focused on the economic cost-effectiveness or impact on transportation costs when using slow-steaming as a means of reducing marine fuel consumption. Moreover, a number of these studies were relying on modeling techniques, by using a limited number of ships and associated routes to determine the effects of slow-steaming. A reasonable degree of agreement emerged from the literature that a reduction in transportation costs results from a reduction in speed, being attributed primarily to reduced fuel costs, with which it is associated. Other cost-increasing factors, such as vessel operating costs, had a less dominant effect. The literature often pointed out that the cost reduction resulting from the application of slow-steaming was unevenly distributed among maritime stakeholders. Shipping companies were the main beneficiaries of significant cost savings, but these "savings" were not always passed on to shippers.
Keywords: 650; Air emissions; Decarbonisation of international shipping; IMO's~short term measure; Least Developed Countries; Slow steaming; Small Island Development States; Sustainable shipping; Transportation cost